RoboKol: A computer program for path planning for redundant and mobile robots - Conkur, Erdinc Sahin (Computer applications in engineering education, 2006)
Redundant manipulators are defined as having an infinite number of solutions to their joint variables. Their many degrees of freedom make them able to determine their configurations to reach the goal point while avoiding obstacles in the workspace. A computer program we named it RoboKol is introduced in this paper, which performs path planning for redundant manipulators and mobile robots using potential field based algorithms. It has been developed in C++ for Windows platforms. Through a friendly user interface, the user can interact with the program and can perform a variety of operations such as drawing obstacles and robots on the screen, obtaining two‐ and three‐dimensional images of the potential field and performing robot simulations. Although RoboKol has originally been developed for research purposes, it is a convenient tool to teach potential fields, path planning for redundant manipulators and mobile robots in engineering education. Comput Appl Eng Educ 14: 198–210, 2006; Published online in Wiley InterScience (www.interscience.wiley.com); DOI 10.1002/cae.20078